Ablation of cardiomyocyte-derived BDNF during development causes myocardial degeneration and heart failure in the adult mouse heart - Li, Lilin; Guo, Hongyan; Lai, Binglin; Liang, Chunbao; Chen, Hongyi; Chen, Yilin; Guo, Weimin; Yuan, Ziqiang; Huang, Ruijin; Zeng, Zhaohua; Liang, Liying; Zhao, Hui; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objective: Brain-derived neurotrophic factor (BDNF) and its receptor TrkB-T1 were recently found to be expressed in cardiomyocytes. However, the functional role of cardiomyocyte-derived BDNF in heart pathophysiology is not yet fully known. Recent studies revealed that BDNF-TrkB pathway plays a critical role to maintain integrity of cardiac structure and function, cardiac pathology and regeneration of myocardial infarction (MI). Therefore, the BDNF-TrkB pathway may be a novel target for myocardial pathophysiology in the adult heart. Approach and Results: In the present study, we established a cardiomyocyte-derived BDNF conditional knockout mouse in which BDNF expression in developing cardiomyocytes is ablated under the control of the Myosin heavy chain 6 (MYH6) promoter. The results of the present study show that ablation of cardiomyocyte-derived BDNF during development does not impair survival, growth or reproduction; however, in the young adult heart, it causes cardiomyocyte death, degeneration of the myocardium, cardiomyocyte hypertrophy, left atrial appendage thrombosis, decreased cardiac function, increased cardiac inflammation and ROS activity, and metabolic disorders, leading to heart failure in the adult heart and eventually resulting in a decrease in the one-year survival rate. In addition, ablation of cardiomyocyte-derived BDNF during the developmental stage leads to exacerbation of cardiac dysfunction and poor regeneration after myocardial infarction (MI) in adult hearts. Conclusions: Cardiomyocyte-derived BDNF is irreplaceable for maintaining the integrity of cardiac structure and function in the adult heart and regeneration after MI. Therefore, the BDNF-TrkB pathway will be a novel target for myocardial pathophysiology in the adult heart. Keywords: Cardiomyocyte, Cardiomyocyte-derived BDNF conditional knockout, Heart failure, Degeneration of the myocardium, Myocardial infarction